(untitled) (Revista Argentina de Musicología, 2024)
In this article, I explore the typical tango orchestras of the traditional style during the sixties in Argentina. I have selected five orchestras of this period: Juan D’Arienzo, Francisco Canaro, Fulvio Salamanca, Héctor Varela and Alfredo De Angelis. First of all, I analyze the progress of the orchestra style of Juan D’Arienzo beetwen the decades 1950 and 1960. This aspect is not frequently adressed in most musicological studies of this orchestra. Then, I explore the recordings of the other orchestras, to identify the role of each one within the traditional esthetic, that is to say, whether they adhere or not to the style of D’Arienzo.